GANplifying event samples - Butter, Anja; Diefenbacher, Sascha; Kasieczka, Gregor; Nachman, Benjamin; Plehn, Tilman (SciPost physics, 2021)
SciPost Journals Publication Detail SciPost Phys. 10, 139 (2021) GANplifying event samples
Gesehen am 13.09.2021